Hatzfeldtsuppe, czyli kuchnia u stóp góry smoka. Rekonesans badawczy kultury kulinarnej Żmigrodu przed 1945 r. .......... 247 - Sobel, Grzegorz (Fantastyczne stwory i bestie w dziejach i kulturze od antyku po czasy najnowsze, 2025)
HATZFELDT SOUP, OR THE CUISINE AT THE FOOT OF DRAGON HILL. A RESEARCH EXPLORATION OF THE CULINARY CULTURE OF ŻMIGRÓD BEFORE 1945The culinary culture of Żmigród before 1945 is a research topic that has not yet been taken up more extensively in the historical literature on the city. The available sources do not allow for a full characterisation of the issue, especially the indication of local differences in relation to Silesian cuisine, the canon of which was established at the turn of the nineteenth and twentieth centuries. The picture of home cooking, bourgeois cuisine, gastronomy, traditions and table customs in the local dimension emerges only from a small number of accounts, without being able to define fully the local culinary culture defined by a historical perspective. The numerous examples cited of the daily diet and festive dishes of the Żmigród inhabitants give only a small idea of their culinary identity. The source deficits, which are so characteristic of small towns in Lower Silesia in the light of the issue under discussion, also make it difficult to present in full the local food producers operating in the town up to 1945 and their products.